Effects of rest interval duration in resistance training on measures of muscular strength: A systematic review - Grgic, J.; Schoenfeld, B. J.; Skrepnik, M.; Davies, T. B.; Mikulic, P. (Sports Medicine, 2018)
Background: Rest interval (RI) duration is an important resistance-training variable underlying gain in muscular strength. Recommendations for optimal RI duration for gains in muscular strength are largely inferred from studies examining the acute resistance training effects, and the generalizability of such findings to chronic adaptations is uncertain. Objective: The goals of this systematic literature review are: (i) to aggregate findings and interpret the studies that assessed chronic muscular strength adaptations to resistance training interventions involving different RI durations, and (ii) to provide evidence-based recommendations for exercise practitioners and athletes. Methods: The review was performed according to the PRISMA guidelines with a literature search encompassing five databases. Methodological quality of the studies was evaluated using a modified version of the Downs and Black checklist. Results: Twenty-three studies comprising a total of 491 participants (413 males and 78 females) were found to meet the inclusion criteria. All studies were classified as being of good to moderate methodological quality; none of the studies were of poor methodological quality. Conclusion: The current literature shows that robust gains in muscular strength can be achieved even with short RIs (< 60 s). However, it seems that longer duration RIs (> 2 min) are required to maximize strength gains in resistance-trained individuals. With regard to untrained individuals, it seems that short to moderate RIs (60-120 s) are sufficient for maximizing muscular strength gains.